Pengaruh Variasi Enzim Lipase Amobil Terhadap Rasio Mol CPO: Metanol Pada Transesterifikasi - Putri Dania, Elisabeth; Aznury, Martha (Jurnal Serambi Engineering, 2025)
Biodiesel is a renewable and environmentally friendly alternative fuel that can be produced from vegetable oils such as Crude Palm Oil (CPO). This study aims to evaluate the effect of varying the mass of immobilized lipase enzyme (12–16 grams) and the molar ratio of CPO to methanol (1:4 and 1:6) on the quality of biodiesel produced through a transesterification process using a Packed Bed Reactor. The process stages include degumming, neutralization, and transesterification at a reaction temperature of 40°C for 6 hours. Immobilized lipase was chosen as the biocatalyst due to its ability to operate under mild conditions and produce high-quality biodiesel without generating harmful waste. The best result was achieved at a 1:4 molar ratio and 15 grams of enzyme, producing biodiesel with a density of 875.67 g/cm³, viscosity of 3.97 mm²/s, saponification value of 177.65 mg KOH/g, acid value of 0.32 mg KOH/g, iodine value of 48.05 g I₂/100 g, cetane number of 66.21, yield of 90.20%, and methyl ester content of 97.31%. All parameters met the Indonesian National Standard (SNI 7182:2015).